The geography of female small business survivorship: Examining the roles of proportional representation and stakeholders - Kalnins, Arturs; Williams, Michele (Strategic Management Journal, 2021)
Abstract Research summary Combining insights from research on firm‐level stakeholders with the well‐established micro literature on social categorization, we develop and test a theory regarding the relative survivorship of female‐owned and male‐owned businesses. The theory is based on proportional representation within geographic areas, defined as each area's female‐owned proprietorship count divided by its total proprietorship count. Analyzing survivorship of over one million proprietorships, we find a robust positive relationship between proportional representation and survival. We then examine effects of local stakeholders such as banks, customers, and network opportunities, in combination with proportional representation. Our research suggests that the effects of female proportional representation are more pervasive than previously considered, influenced by communities of business stakeholders, and, in some cases, leveling the playing field for female entrepreneurs. Managerial summary We analyzed relative survival duration of one million female‐ and male‐owned proprietorship businesses. We argued that a higher proportional representation of female business owners among all owners in a geographical area would combat negative stereotypes about women's business competence. We found that female‐owned businesses survived relatively longer than their male‐owned counterparts in areas with substantial proportional representation of female owners and that the relative benefits for women were magnified in the presence of local banks (which provide capital) as well as in customer‐rich and network‐rich areas. Business ownership has been proposed to be a “great equalizer” for women frustrated by the glass ceilings of corporate employment. We find this is true, but only in areas with a high proportional representation of women among business owners.